Menstruation practice among school and out-of-school adolescent girls, Lao PDR - Sychareun, Vanphanom (Glob Health Action, 2020)
BACKGROUND: The transition from childhood to adolescence is a critical transitional period for girls, and as they experience these changes, having knowledge of, and being able to practice, good menstruation hygiene management is crucial. The objective of this study was to understand in and out of school adolescents’ menstrual hygiene management practice, sources of information and attitudes towards menstruation. METHODS: A cross sectional, descriptive study was conducted between November 2018 and May 2019. The sampling included adolescent girls aged 11–19 years in higher secondary schools in Khammouane and Champassak provinces and out-of-school adolescent girls. Out of the total number of 433 participants enrolled in the study, only 343 girls had reached menarche and were included in the study. Factors associated with menstruation hygiene management practice were examined with bivariate and multivariate analyses. RESULTS: Out of 343 subjects who had reached menarche, 44% reported good menstrual hygiene management practice. Over half of the participants, however, were unable to access the tools of good menstruation hygiene management practice, including having somewhere to dispose of used sanitary pads in private. Being older (16–19 years) (AOR:2.4; 95%CI 1.4 to 3.9), and having primary education (AOR 0.4; 95%CI 0.2 to 0.9) were associated with good practice as was fathers’ level of education (AOR 2.1; 95%CI 1.0 to 4.1) and mother-girl discussion about menstruation (AOR 2.2; 95%CI 1.0 to 5.0). No significant differences were found between in- and out-of-school adolescents. CONCLUSIONS: In this study, not all participants were able to practice optimal menstruation hygiene management. This is important as good menstrual hygiene management is associated with better health and being able to participate fully in education and work. Further education is needed, but it is also important to ensure that all adolescent girls have access to the necessary tools for effective menstruation hygiene management.